PENGARUH UKURAN PERUSAHAAN, LEVERAGE TERHADAP AGRESIVITAS PAJAK PADA PERUSAHAAN OTOMOTIF YANG TERDAFTAR DI BURSA EFEK INDONESIA - Alhamida Oktavia Ningrum; Supar Wasesa; Nur Augus Fahmi (JRMB (Jurnal Riset Manajemen & Bisnis), 2021)
The purpose of this research is to determine the influence of company size, and leverage against tax aggressiveness on automotive companies registered with IDX. So that the problems in this study do not extend, then this paper raises the topic of the burden of corporate size, and leverage against tax aggressiveness. This research is limited to automotive companies registered with IDX. In this study, the sampled companies are automotof sector companies listed on the Indonesia Stock Exchange. The data used in this study is from 2015-2018. The population in this study amounted to 5 companies. To determine the sample size that can represent the population, the selection of samples using purposive sampling method, namely as many as 5 companies This research approach is an associative approach with quantitative data types. The testing method uses multiple linear regression analysis techniques using SPSS version 21. Based on the results of testing and analysis shows that there is a positive and significant influence of tax returns on tax aggressivity, leverage has no significant effect on tax aggression, and the influence of corporate size and leverage silmutan on tax aggression on automotive companies listed on the Indonesia Stock Exchange.